Glucagon and glucose counterregulation: pancreatic α-cell function and dysfunction during hypoglycaemia - Hamilton, A (2018)
The glucagon-secreting α-cell is vital for the maintenance of glucose homeostasis and prevention of hypoglycaemia. Despite its importance many aspects of α-cell physiology are disputed. Thus, in this thesis, I aimed to elucidate several features of α-cell function – exploring how autonomic signals are integrated by the cell and how diabetes leads to its dysfunction. The autonomic response to hypoglycaemia results in increased acetylcholine and adrenaline in the islet vicinity, which stimulate glucagon secretion. The mechanisms underlying these effects were investigated using live [Ca2+]i imaging and patch-clamp electrophysiology. Adrenaline was found to target the α-cell via a β-adrenergic mechanism, inducing TPC2-mediated Ca2+ release from the (endo)lysosomal stores, which triggered calcium-induced calcium release from the endoplasmic reticulum (ER). Acetylcholine also induced ER Ca2+-release via muscarinic Gq signalling. However, a component of the effect resulted from activation of a nicotinic pathway that evoked P/Q-type Ca2+ channel influx. The glucagon response to hypoglycaemia is lost in diabetes. To investigate the effect of hyperglycaemia on α-cell function at low glucose, the Fh1βKO type 2 diabetic mouse model was used. In these mice, prolonged hyperglycaemia led to blunted glucagon secretion at low glucose. Using live pH imaging, it was shown that this was caused by hyperglycaemia increasing flux through Na+ coupled glucose transporters (SGLTs), disrupting Na+-dependent acid extrusion and inducing cytoplasmic acidification. The resulting build-up of protons was speculated to compromise mitochondrial ATP production leading to the observed glucagon secretory defects. The effects of insulin-induced hypoglycaemia on δ-cell [Ca2+]i activity were also investigated. Increased SGLT2 transport and low [K+]o, features of insulin-induced hypoglycaemia, were both shown to increase [Ca2+]i activity in δ-cells, stimulating somatostatin secretion and consequently suppressing glucagon secretion. Together these data suggest that glucagon secretion at low glucose is lost due to the combined effects of hyperglycaemia-driven intrinsic dysfunction and insulin-induced somatostatin secretion.